Cadmium Sulfide Thin Films Deposited onto MWCNT/Polysulfone Substrates by Chemical Bath Deposition - M. Moreno; G. M. Alonzo-Medina; A. I. Oliva; A. I. Oliva-Avilés (Advances in Materials Science and Engineering)
Cadmium sulfide (CdS) thin films were deposited by chemical bath deposition (CBD) onto polymeric composites with electric field-aligned multiwall carbon nanotubes (MWCNTs). MWCNT/polysulfone composites were prepared by dispersing low concentrations of MWCNTs within dissolved polysulfone (PSF). An alternating current electric field was “in situ” applied to align the MWCNTs within the dissolved polymer along the field direction until the solvent was evaporated. 80 μm thick solid MWCNT/PSF composites with an electrical conductivity 13 orders of magnitude higher than the conductivity of the neat PSF were obtained. The MWCNT/PSF composites were subsequently used as flexible substrates for the deposition of CdS thin films by CBD. Transparent and adherent CdS thin films with an average thickness of 475 nm were obtained. The values of the energy band gap, average grain size, rms roughness, crystalline structure, and preferential orientation of the CdS films deposited onto the polymeric substrate were very similar to the corresponding values of the CdS deposited onto glass (conventional substrate). These results show that the MWCNT/PSF composites with electric field-tailored MWCNTs represent a suitable option to be used as flexible conducting substrate for CdS thin films, which represents an important step towards the developing of flexible systems for photovoltaic applications.